2023
DOI: 10.3390/ejihpe13050068
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Drug Consumption among Drivers before and during the COVID-19 Pandemic: An Observational Study

Abstract: Restrictions imposed during the COVID-19 pandemic might have changed recreational habits. In this study, the results of toxicological tests for alcohol and drugs in blood were compared among drivers stopped at roadside checks in the periods before (1 January 2018 to 8 March 2020) and after the lockdown measures (9 March 2020 to 31 December 2021). A total of 123 (20.7%) subjects had a blood alcohol level above the legal limit for driving of 0.5 g/l, 21 (3.9%) subjects tested positive for cocaine, and 29 (5.4%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…For instance, a study conducted in Germany demonstrated that trait (predisposition) loneliness rather than state (momentary) loneliness was positively associated with alcohol consumption during the pandemic [40]. This might explain why toxicological tests for alcohol and drugs in drivers stopped at roadside checks increased not only during lockdown but also during the rest of the pandemic [41], and our findings of a significant rate of alcohol intoxication in many trauma patients align very well with such evidence.…”
Section: Neurotraumasupporting
confidence: 85%
“…For instance, a study conducted in Germany demonstrated that trait (predisposition) loneliness rather than state (momentary) loneliness was positively associated with alcohol consumption during the pandemic [40]. This might explain why toxicological tests for alcohol and drugs in drivers stopped at roadside checks increased not only during lockdown but also during the rest of the pandemic [41], and our findings of a significant rate of alcohol intoxication in many trauma patients align very well with such evidence.…”
Section: Neurotraumasupporting
confidence: 85%